Bacillus spp. Isolated from Puba as a Source of Biosurfactants and Antimicrobial Lipopeptides - Perez, Karla J.; Viana, Jaime dos Santos; Lopes, Fernanda C.; Pereira, Jamile Q.; dos Santos, Daniel M.; Oliveira, Jamil S.; Velho, Renata V.; Crispim, Silvia M.; Nicoli, Jacques R.; Brandelli, Adriano; Nardi, Regina M. D. (Frontiers in Microbiology, 2017)
Several products of industrial interest are produced by Bacillus, including enzymes, antibiotics, amino acids, insecticides, biosurfactants and bacteriocins. This study aimed to investigate the potential of two bacterial isolates (P5 and C3) from puba, a regional fermentation product from cassava, to produce multiple substances with antimicrobial and surface active properties. Phylogenetic analyses showed close relation of isolates P5 and C3 with Bacillus amyloliquefaciens and Bacillus thuringiensis, respectively. Notably, Bacillus sp. P5 showed antimicrobial activity against pathogens such as Listeria monocytogenes and Bacillus cereus, in addition to antifungal activity. The presence of genes encoding pre-subtilosin (sboA), malonyl CoA transacylase (ituD), and the putative transcriptional terminator of surfactin (sfp) were detected in Bacillus sp. P5, suggesting the production of the bacteriocin subtilosin A and the lipopeptides iturin A and surfactin by this strain. For Bacillus sp. C3 the presence of sboA and spas (subtilin) genes was observed by the first time in members of B. cereus cluster. Bacillus sp. P5 showed emulsifying capability on mineral oil, soybean biodiesel and toluene, while Bacillus sp. C3 showed emulsifying capability only on mineral oil. The reduction of the surface tension in culture medium was also observed for strain P5, confirming the production of surface-active compounds by this bacterium. Monoprotonated molecular species and adducts of sodium and potassium ions of surfactin, iturin and fengycin were detected in the P5culture medium. Comparative MS/MS spectra of the peak m/z 1030 (C14 surfactin A or C15 surfactin B [M+Na]+) and peak m/z 1079 (C15 iturin [M+Na]+) showed the same fragmentation profile of standards, confirming the molecular identification. In conclusion, Bacillus sp. P5 showed the best potential for the production of antifungal, antibacterial and biosurfactant substances.